2023
DOI: 10.1177/02676591231193977
|View full text |Cite
|
Sign up to set email alerts
|

Effect of peri-operative intra-aortic balloon pump in patients undergoing coronary artery bypass grafting on outcomes in a resource limited setting

Abdul Ahad Sohail,
Areeba Samejo,
Hamza Bajwa
et al.

Abstract: Introduction Intra-aortic balloon pump (IABP) insertion for diminished myocardial function is standard of care in cardiac surgery. Previous studies have suggested a possible benefit to IABP support before surgery with regards to outcomes and complications. However, there are conflicts with other studies suggesting no significant benefit. Optimal time of insertion, whether preoperative or perioperative (intra-operative and post-operative), has yet to be defined. Methodology A retrospective, hospital records-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…15 Suhail et al reported improved mortality in high risk patients with pre-operatively inserted IABP. 16 We compared the intra-operative and post-operative parameters of patients who had IABP utilized and in those without IABP. Patients from the IABP group were on average around 3 years older.…”
Section: Discussionmentioning
confidence: 99%
“…15 Suhail et al reported improved mortality in high risk patients with pre-operatively inserted IABP. 16 We compared the intra-operative and post-operative parameters of patients who had IABP utilized and in those without IABP. Patients from the IABP group were on average around 3 years older.…”
Section: Discussionmentioning
confidence: 99%